PRIVATE SENIOR HIGH SCHOOL TEACHERS’ SELF-EFFICACY IN UNDERSTANDING STUDENTS’ NEEDS DURING THE ONLINE LEARNING - Agustine Andriana Ayu Mahardika; Concilianus Laos Mbato (Widya Mandala Surabaya Catholic University, 2022)
During the pandemic, everyone is required to do activities at home, including the teaching-learning process, which is done online. Students’ needs should be taken seriously by teachers. High self-efficacy is essential, and teachers must regulate their emotions in teaching students online learning. This research aimed to determine teachers’ self-efficacy in understanding students’ needs and strategies for regulating their emotions during online teaching-learning. During the teaching-learning process, teachers may face various students’ characteristics, and sudden situations that happen during the process may stress the teachers. Therefore, teachers need self-efficacy that will help them regulate themselves to execute their actions and solve problems. This qualitative research employed an open-ended questionnaire distributed to five private senior high school teachers, and an in-depth interview was conducted with three private senior high school teachers. The findings revealed that self-efficacy and emotion-regulation strategies were the main factors for teachers to understand their students’ needs during the teaching-learning process. It is recommended that future researchers interested in expanding this topic do extensive research to check its trustworthiness and provide further information about it.